Cytogenetics of three species of scorpions of the genus Brachistosternus from Argentina (Scorpiones: Bothriuridae) - Rodríguez Gil, Sergio Gustavo (2009)
Meiotic studies on three phylogenetically distant species of the genus Brachistosternus Pocock from Argentina were conducted. One species is from the subgenus Ministernus Francke 1985, B. ferrugineus Thorell 1876, and two species are from the subgenus Brachistosternus Pocock 1893, B. montanus Roig-Alsina 1977 (Andean species group), and morphologically different populations of B. pentheri Mello-Leitão 1931 (plains species group). All species showed achiasmatic meiosis, absence of heteromorphic bivalents, and bibrachial and monobrachial chromosomes of different sizes. Males of Brachistosternus ferrugineus, B. montanus, and one population of B. pentheri have 2n 46. Males of the typical populations of B. pentheri have 2n 42. These results suggest that B. pentheri may comprise two species.